Effectiveness of the Nearpod Platform within the Discovery Learning Model to Enhance Students’ Learning Motivation and Learning Outcomes on Reaction Rate Topic - Nihla Anandita; Netti Herawati; Muhammad Jasri Djangi (Jambura Journal of Educational Chemistry, 2025)
This study aims to evaluate the effectiveness of nearpod platform integrated within the discovery learning model in enhancing students' motivation and learning outcomes in reaction rate material. The research employs a pre-experimental one-group pretest-posttest design. The subjects were 39 students of class XI KIMIA 3 at SMA Negeri 9 Makassar. Data were collected through pretests and posttests. The motivation and learning outcomes data were analyzed descriptively and inferentially. Descriptive analysis was performed using N-gain, which revealed an average N-gain of 0.35 (moderate) for motivation and 0.72 (high) for learning outcomes. Inferential analysis for the motivation data was conducted using the Wilcoxon Signed-Rank Test. The results indicated Z observed value = 2.04 and Z critical value of 1.65, that leading to the rejection of H₀ and acceptance of H₁. inferential analysis for learning outcomes was performed using a one-sample t-test. The results showed t observed value = 21 and t critical value = 1.68, leading to the rejection of H₀ and acceptance of H₁. Based on the data analysis, it can be concluded that the platform nearpod is effective in enhancing the motivation and learning outcomes of students.